Barriers to positive policy change that aims to increase access to medicines through reclassification: the case of oseltamivir in New Zealand. (7th July 2015) - Shaw, John P; Gauld, Natalie; Kelly, Fiona
Abstract: Objectives: This study aims to identify and explore emergent barriers to consumers accessing oseltamivir without prescription following policy change introduced in New Zealand to increase access via community pharmacies. Methods: Semi-structured interviews were conducted with 26 community pharmacists immediately following the first season of oseltamivir availability without prescription in October 2007. Interviews were transcribed verbatim and coded using a framework approach to identify themes. Key findings: Non-prescription sales of oseltamivir were slow during this period. Participants acknowledged that they may have missed opportunities to recommend oseltamivir and attributed this to a range of reasons. Pharmacy-related barriers identified included limited pharmacist confidence, concerns about efficacy and safety of the product, location of the product in the pharmacy, affordability and the role of support staff. Many pharmacists adopted a 'risk-benefit analysis' that balanced symptom severity with perceived value for money. Consumer barriers included cost, limited awareness of availability and limited ability to correctly self-diagnose and manage influenza. Conclusions: Complexity in the factors that influenced pharmacist motivation to supply oseltamivir without prescription highlighted the potential for positive policy change to be hindered by multiple barriers. Greater understanding of such barriers is important for effective transition of medicines from prescription to non-prescription availability to achieve increased consumer access through reclassification. Concerns that pharmacists are influenced by commercial priorities when medicines are newly reclassified were not substantiated in this study.